SPECIFIC FEATURES OF THE DEVELOPMENT OF THE SPIRITUAL AND SOCIAL LIFE OF THE KARAKALPAK PEOPLE IN THE AWARENESS OF NATIONAL IDENTITY - Saparova, G.A. (SCIENCE and SOCIETY, 2026)
The article discusses the development of the spiritual and social life of the Karakalpak people, including their national language, customs, traditions, unique cultural wealth, and some types of art. In addition, concepts such as history, culture, fiction, religious beliefs, and national values of the Karakalpak people are described in archeology, ethnography, folklore studies, art studies and other subjects. Also, in the conditions of today's globalization, it occupies a special place in the constantly increasing need for national identity.
Keywords: culture; spirituality; art; custom; tradition; nation; identity; value; religious faith; fiction; history of the Karakalpak people; archeology; ethnography; folklore